2021
DOI: 10.1002/jcop.22573
|View full text |Cite
|
Sign up to set email alerts
|

Exploring factors related to supportive housing tenure and stability for people with serious mental illness

Abstract: Overall, the retention of people with serious mental illness (SMI) in supportive housing is high. However, some supportive housing settings report average stays of only 15 months, and others report declines in housing retention over time. Many studies report variables associated with supportive housing stability and tenure, but there are few extensive, focused investigations on the subject. Hence, a literature review was conducted to investigate factors associated with supportive housing stability and tenure a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 58 publications
0
3
0
1
Order By: Relevance
“…As people with SMI move residences more often than the general population (Lix et al, 2006), perhaps many people cannot take advantage of the benefit of living in a place for a long time. The body of knowledge in housing stability identified that sense of community is a major factor that made people live in one place for a longer period of time (Leickly & Townley, 2021). It appears consistent that helping newcomers feel included and that they belong in the community is a way to enhance both housing satisfaction and housing duration.…”
Section: Discussionmentioning
confidence: 99%
“…As people with SMI move residences more often than the general population (Lix et al, 2006), perhaps many people cannot take advantage of the benefit of living in a place for a long time. The body of knowledge in housing stability identified that sense of community is a major factor that made people live in one place for a longer period of time (Leickly & Townley, 2021). It appears consistent that helping newcomers feel included and that they belong in the community is a way to enhance both housing satisfaction and housing duration.…”
Section: Discussionmentioning
confidence: 99%
“…Research in social psychology has found that contact-based approaches produced the best results in comparison to other destigmatization strategies – such as protests aimed at chastising offenders for their negative attitudes and behaviours or education programmes aimed at dismissing stereotypes with factual information (Corrigan & Bink, 2016). Thus, sustained contact with the community may significantly reduce mental illness stigma (Leickly & Townley, 2021) and social enterprises can play an important role here (Farmer et al, 2016; Roy et al, 2014). Extant research has investigated how WISEs do so, for instance, by hosting community events such as concerts that bring the beneficiaries and the community together and help the latter ‘develop a positive impression of the business and its workers’ (Lysaght et al, 2012, p. 460).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…When reintegrating disadvantaged people, the cooperation of the community at large has been found to be particularly relevant. To this aim, prosocial organizations carry out community work that facilitates encounters between the disadvantaged and community members (Leickly & Townley, 2021; Roy, Donaldson, Baker, & Kerr, 2014). Disadvantaged people, in fact, often suffer from stigmatization which hinders their social reintegration and can also carry negative consequences for the organizations helping them (Tracey & Phillips, 2016).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…자립에 대한 개념을 적용한 국내 연구들은 대부분 지원주택, 자립생활 주택, 독립주거와 같이 주거지를 기준으로 하는 자립 생활에 관한 질적연구들이며 [6,[10][11][12][13] 국외 연구에서도 지지 주거형태의 주거지를 기준으로 실증분석을 진행하여 지지 주 거를 유지하는 요인을 살펴보았다 [16]. 주거지 유형에 따른 자 립생활 주택 [19]에 관한 연구결과는 일상생활과 정신과적 증 상 관리가 중심이며, 지원주거 [11,[14][15][16][17][18][19] 유형의 자립을 다룬 연구의 결과는 자신의 일상생활 문제 해결 능력이 자립의 중심 이라고 보고 있었다. 또한 독립주거 [20] 유형의 자립에 관한 연 구결과는 자립생활에 참여하는 사람의 상황 차이를 고려한 독 립주거 준비단계의 필요성을 제시하였고 사회복지학에서 연 구한 자립생활 경험 [6], 자립생활 성공 경험 [10]…”
unclassified